Sulfated polysaccharides of Green Algae: Chemical Composition and Antioxidant Activity in vitro of Fractionated Ulvans from Ulva lactuca and Ulva papenfussii - Tran, Vy Ha Nguyen; Nguyen, Thuan Thi; Cao, Hang Thi Thuy; Vo, Mai Nhu Hieu; Tran, Thi Thanh Van; Pham, Duc Thinh; Huynh, Hoang Nhu Khanh; Nguyen, Ngoc Linh; Nguyen, Dinh Thuat (Vietnam Journal of Marine Science and Technology, 2025)
The study evaluated the chemical composition, molecular weight, and antioxidant activity of ulvan extracted from Ulva papenfussii and Ulva lactuca. The results revealed distinct differences in the monosaccharide composition, sulfate content, and uronic acid levels between ulvans from both species, with ulvan from U. papenfussii exhibiting higher levels of iduronic acid and sulfate (16.39 ± 0.45 %w/w and 28.46 + 3.63 %w/w). Ulvan was fractionated using anion exchange chromatography (DEAE) based on charge differences, yielding three main fractions from each species. This study is the first to analyze different ulvan fractions from Vietnamese green algae using the anion exchange chromatography method. The antioxidant activity of the ulvan fractions was determined by their ability to DPPH radical scavenging activity, reducing power activity, and antioxidant activity, with UL2 (29.5 ± 0.94 Sc%) and UP2 (25.9 ± 1.77 Sc%) demonstrating the most prominent results. These active fractions were characterized by higher sulfate and uronic acid content, suggesting a potential structure–activity relationship. These findings highlight the potential of ulvan in the food and pharmaceutical industries.